Obama's energy policy: the crucial role of coal in the US climate legislation - Robinson, D (Oxford Institute for Energy Studies, 2009)
If a bomb was ticking and could explode at any moment, you would do everything possible to defuse it right away. The problem of climate change resembles a ticking bomb. Yet the global response to this bomb has been slow and inadequate. There are many reasons, including the absence of global leadership, the difficulties of collective action in the international system, the uncertainty about when and where the bomb will explode, and the preference to let others do the heavy lifting. One other reason for the slow response is that protecting or compensating the potential losers often weakens the environmental integrity of the legislation. This matters less where a small country is concerned. However, weak climate legislation in the USA will undermine global efforts to fight climate change. This article examines some of the pressures that have weakened the environmental integrity of the American Clean Energy and Security Act (ACESA), which recently passed through the House of Representatives. Producers and consumers of coal and of coal-based electricity (i.e. the ‘coal lobby’, including companies, workers and consumers of different sizes in these sectors and more generally citizens in the regions where the companies operate) are the main losers from climate legislation; compensating them and helping them to prepare for the future has come at a price. This article has four sections. First, it summarises the challenges of climate change and the importance of cutting coal emissions from existing coalfired power plants, especially in the USA and China. Second, it discusses some of the reasons why ACESA is coming up short. Third, it illustrates how this draft US legislation has been weakened in order to obtain support from affected parties, especially those relying on coal and coal-based electricity. And, finally, it draws some conclusions. The reader should take away two messages. First, the pressure to weaken the environmental integrity of ACESA in the US Senate will be intense; it is important for the Administration to resist that pressure. Second, there is no credible way to stabilise greenhouse gas emissions without cutting emissions from existing coal plants. US legislation should focus on cutting emissions from existing (not just new) coal plants and providing economic incentives for this to happen as soon as possible in the USA and China.